(untitled) (Journal of Engineering, 2024)
In civil engineering, there are many problems related to the transmission of pressure waves through the soil due to dynamic loads. In industrial applications, these vibrations remain often caused by the impact of weights on the foundation machine. Typically, these basics transmit effective vertical stresses to the surface layers. Accordingly, the dynamic performance of natural clay soils under the influence of individual active loads was careful in this work. Energy A deflection scale system dropped different loads from several elevations. The application of this research was to study the surface soil responses only. These responses include the vertical displacements, velocities, and accelerations implied by impacts on the soil surface. Some of the results showed a decrease in the displacement value of the natural clay soil by a rate ranging from 25% to 35%, a result of an increase in the overburden pressure based on an increase in the embedment depth, which led to a rise in the stiffness of the clayey soil.